Opinions of pediatric nurses about Jehovah’s Witnesses refusal of blood transfusion for their child - Jakubowska, Klaudia; Kuczek, Barbara; Wiśniewska, Anna; Pilewska-Kozak, Anna; Dobrowolska, Beata (Nursing in the 21st Century, 2018)
OPINIONS OF PEDIATRIC NURSES ABOUT JEHOVAH’S WITNESSES REFUSAL OF BLOOD TRANSFUSION FOR THEIR CHILDIntroduction. Jehovah’s Witnesses absolutely refuse having blood transfusion performed. The situation is even more difficult when the refusal of blood transfusion concerns a child. Despite existing legal solutions, medical staff experiences value conflicts. Aim. To analyze the opinions of pediatric nurses about problems that may arise in case of Jehovah’s Witnesses refusal of blood transfusion for their child.Material and methods. Quantitative research was based on a diagnostic survey method. The variables were measured with the use of a survey questionnaire co-developed by the authors. A group of 104 pediatric nurses from the South-East Poland participated in the study.Results. To the question “Have you ever encountered the situation throughout all your working career when parents refused their child to undergo a blood treatment due to their beliefs?”, 67.31% (n = 70) of the respondents replied the situation rarely happened. Half of the nurses surveyed (n = 52, 50.02%) admitted they did not accept the position of Jehovah’s Witnesses concerning blood treatment. Most of the nurses surveyed – 87.38% (n = 89) think the existence of procedures on how to proceed in this difficult situation is crucial, and 83% (n = 86) of the respondents admitted that there was no better solution than the already existing legal procedure.Conclusions. The most difficult experience of pediatric nurses in the situation of Jehovah’s Witnesses refusal of blood transfusion for their child is in the opinion of surveyed nurses, endangering the child’s health or even life. Thus, most of the respondents agree that the best solution in that case is to implement a legal procedure that allows blood transfusion despite parents’ refusal.